Thermoluminescence study of semiconductor materials SixTe60−x As30Ge10 - Maged, A.F.; Amin, Y.M.; Durrani, S.A. (Springer Verlag (Germany), 1992)
The effect of gamma irradiation on SixTe60−xAs30Ge10, where x= 5, 12 and 20, has been studied using thermoluminescence (TL). As expected in semiconductor materials, both x=5 and 20 chalcogenides showed a wide TL peak ranging from ∼80–300 °C. However, these two materials also exhibited a sharp peak at ∼360 and ∼380 °C for x = 5 and 20, respectively. On the other hand, the material with x=12 showed very little response to gamma radiation, but if the sample was exposed to ultraviolet light (after being glowed of any TL up to 500°C) and then glowed (called phototransfer-thermoluminescence), several peaks appeared at ∼80, 180, 300, and 350°C. The x= 5 and 20 samples did not show any response to ultraviolet light. Because the TL response depended on the ratio of Te/Si, it can be concluded that the TL technique can also be used to characterize semiconductor materials, and it would complement other techniques such as electrical conductivity and differential thermal analysis.